Conceptualizing intercultural communicative competence in higher education in the Japanese context: Insights from language learners, practitioners, and public arena - Yoko Munezane (Social Sciences and Humanities Open)
Intercultural competence has primarily been conceptualized from a theoretical standpoint mainly by scholars in the U.S. and Europe in academic discourse. Moreover, there is a paucity of attempts to define and model intercultural communicative competence, through inductively collecting data. The current study aims to provide the definitions of intercultural competence and present a new conceptual model of intercultural communicative competence in the understudied context: Japan. The study synthesizes the insights from understudied three groups of key stakeholders; language learners, language teachers, and people in the public arena, through empirically and inductively collecting the definitions of intercultural communicative competence from each party. The data were collected through a web-based survey and semi-structured interviews, and analyzed using a qualitative content analysis approach, combining concept-driven strategies and data-driven strategies. The key findings were that the learners, in general, placed high emphasis on proactiveness in communication, and Grit (passion and perseverance). In contrast, teachers, in general, emphasized the importance of focusing on similarities across cultures, and common ground for humanity for mutual understanding. On the other hand, people in the public arena emphasized logic and comprehensive human power as universal resources for intercultural competence. A new model of intercultural competence was developed, synthesizing perspectives from three groups of stakeholders.